Physical-sports activity as a protective factor in the initiation of tobacco consumption - Sota Rodrigo, Cristina; Mercado Val, Elvira (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Objective: To demonstrate the relationship between sport as a protective factor in the onset of tobacco Development: Retrospective cohort study during 2018-19 in 24 centers (2404 students aged 12-19 years), 49% boys and 51% girls answering 43 items. Results: 67.2% who do not smoke practice sport several times a week and 29.5% daily. They spend their free time with friends (80.1%), TV (50.4%), bars and discotheques (7.5%), clubs (4.5%) and the street (4.4%). Smokers: friends (81.9%), street (50.9%), tv (40.5%), clubs (4.3%), bars and discotheques (3.4%). Conclusions: High significance of sport related to smoking, age and gender.